p6unkeJswSamml
p6unkeJswSamml
04-01-2016
Mathematics
contestada
Simplify 6 - (-2) - 3(-5).
Respuesta :
Billymkhoi
Billymkhoi
04-01-2016
6- (-2) - 3(-5)
= 6- (-2) +15
= 6+ 2 +15
= 8+ 15
=23.
The final answer is 23
.
Answer Link
Exvited
Exvited
04-01-2016
[tex]6 - (-2) - 3(-5) \\ \\ 6 + 2 + 15 \\ \\ 23 \\ \\ \fbox {23} [/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 27+ )
Otras preguntas
find the value of k in the equation 5k+1=10.which answer is correct 'first or second?then why? ans(1) : 5k+1=10 5k=10-1 5k=9
What is the LCD of and ? 34 17 19 1
That trait is described as a person being very thin skinned; someone who is hypersensitive and others ot knowing what sets them off?
(3, 5), (−3, r), m=34
List 10 jobs career in cookery
If the difference of p(x)=ax^4/5 + x^3/3 -2x^2/5 + bx/7 -1 and q(x)= x^4/5 + x^3/4 -1/3 x^2 +1/2 x + 3 is h(x) =1/5 x^4 + 1/12 x^3 - 1/15 x^2 + 5/14 x - C then
can someone pls help with this, I would appreciate it
Correct the one error. (IXL, IAR Practice Testing)
6. Convert from radians to degrees. 22 15 O O 528° 264° 132° 792°
a3 -a2 b2 +b3 when a=(-2) and b=(-1)